From Current Understanding to Future Perspectives in Sjögren’s Syndrome: An Integrated Literature Review and Analysis of Emerging Trends - Lisboa Rennó, Andre; Cateb Resende de Oliveira, Bruno; Bosshard Pereti R. Martinho Calsavara, Guilherme; Henrique Montera Lucilio, Guilherme; Slindvain Bagnariolli Freitas, Pedro; Abdul Hadi EI Khatib , Shadia; Torquato Viana , Victoria (InterAmerican Journal of Medicine and Health, 2025)
Sjögren's Syndrome is a chronic autoimmune disease that primarily affects the exocrine glands, leading to dryness of the eyes and mouth. The pathogenesis of the disease involves a complex interplay between immune dysregulation, inflammation, and glandular dysfunction. This article presents an overview of the pathophysiology of Sjögren's Syndrome, including the functional alterations and immune responses involved. Additionally, current therapeutic options, including replacement and retention therapy, stimulation of glandular production, and modulation of the immune response, are discussed. Future directions for research in developing more specific and effective therapies for Sjögren's Syndrome are also presented.